Improving Patient Care Through Nursing Engagement in Evidence‐Based Practice. Issue 2 (13th January 2016) - Crabtree, Elizabeth; Brennan, Emily; Davis, Amanda; Coyle, Andrea
Abstract : This column shares the best evidence‐based strategies and innovative ideas on how to facilitate the learning of EBP principles and processes by clinicians as well as nursing and interprofessional students. Guidelines for submission are available athttp://onlinelibrary.wiley.com/journal/10.1111/(ISSN)1741‐6787